Promoting Effective Decision Making: Training Educators to Collect and Use Social–Emotional Skill Assessment Data to Inform Tier 2 Interventions. Issue 5 (11th October 2022) - von der Embse, Nathaniel Paul; Kilgus, Stephen P.; Eklund, Katie; Zahn, Miranda; Peet, Casie; Durango, Sarahy
Abstract: Teachers are often called upon to identify students at behavioral and emotional risk by completing a variety of assessment tools. However, many teachers may lack the requisite skills to reliably identify students at risk or use data derived from assessment tools to inform intervention. A series of trainings was developed to improve decision making on the Intervention Selection Profile–Social Skills, with a focus on improving accuracy and use of data. Specifically, a two-study randomized controlled design was employed to evaluate the efficacy of a basic informational training and a training with a practice component with regards to a control condition on the collection and use of social–emotional assessment data on the ISP-SS. Results suggest limited influence of training on the accuracy of data collection, yet significant influence on improving how data are used to inform intervention. Implications for practice and research, as well as limitations, are discussed.